Amplicon-Based Sequencing of Soil Fungi from Wood Preservative Test Sites - Kirker, Grant T.; Bishell, Amy B.; Jusino, Michelle A.; Palmer, Jonathan M.; Hickey, William J.; Lindner, Daniel L. (Frontiers in Microbiology, 2017)
Soil samples were collected from field sites in two AWPA (American Wood Protection Association) wood decay hazard zones in North America. Two field plots at each site were exposed to differing preservative chemistries via in-ground installations of treated wood stakes for approximately 50 years. The purpose of this study is to characterize soil fungal species and to determine if long term exposure to various wood preservatives impacts soil fungal community composition. Soil fungal communities were compared using amplicon-based DNA sequencing of the internal transcribed spacer 1 (ITS1) region of the rDNA array. Data show that soil fungal community composition differs significantly between the two sites and that long-term exposure to different preservative chemistries is correlated with different species composition of soil fungi. However, chemical analyses using ICP-OES found levels of select residual preservative actives (copper, chromium and arsenic) to be similar to naturally occurring levels in unexposed areas. A list of indicator species was compiled for each treatment-site combination; functional guild analyses indicate that long-term exposure to wood preservatives may have both detrimental and stimulatory effects on soil fungal species composition. Fungi with demonstrated capacity to degrade industrial pollutants were found to be highly correlated with areas that experienced long-term exposure to preservative testing.